Contributions of Formal Education to Social Development – What do we Know on the Basis of Research Evidence? - Takala, Tuomas (Journal of Education and Research, 2010)
This article gives an overview, on the basis of existing synthesis reports and articles, of the current state of knowledge on the role of formal education in promoting social development. The existing evidence is contrasted with simplistic assumptions that abound in the political discussions on education and development. At the same time, the limitations of the potential of research to serve as a guide to policy decisions are also acknowledged. DOI: http://dx.doi.org/10.3126/jer.v2i0.7616 Journal of Education and Research Vol. 2, 2010 p.1-8